Menyiapkan Guru Masa Depan: Pelatihan Strategis Penulisan Proposal Penelitian bagi Mahasiswa - Gunawan, Gunawan; Harjono, Ahmad; Herayanti, Lovy (Indonesian Publication Center, 2023)
The ability to compile a research proposal is a crucial competence for students, especially for pre-service teachers who are prepared to become professional educators with scientific literacy. However, obstacles in formulating ideas, determining research methods, and a lack of knowledge regarding the publication process often hinder the timely completion of their studies. This community service activity aims to provide strategic mentoring in writing research proposals, understanding methodologies, and scientific publication techniques. The activity was attended by 50 students of the Faculty of Teacher Training and Education, University of Mataram. The implementation method was carried out through a series of training sessions covering introduction to writing, in-depth research methods, strategies for selecting target journals, and technical submission simulations. The results showed high participant enthusiasm and a significant increase in understanding regarding the research flow from the proposal stage to potential publication. Through this training, students are not only prepared to complete their final projects but also equipped with essential research skills for their future teacher professionalism.